Gender and Culturally Responsive School Leadership: A Quantitative Study of Elementary Principals’ Florida’s Panhandle - Jones, Nickitra D.; Elmahdy, Sherin Y.; Aly, Ezzeldin R. (European Scientific Journal, ESJ, 2026)
As student populations in U.S. public schools become increasingly diverse, educational leaders face ongoing challenges in addressing educational disparities and fostering equitable learning environments. Culturally responsive school leadership (CRSL) has emerged as an important framework for understanding how principals develop inclusive practices, strengthen school communities, and respond to the cultural assets and needs of diverse learners. Grounded in CRSL theory, this quantitative study examined elementary school principals’ culturally responsive leadership practices in Florida’s Panhandle, with particular attention to whether reported practices differed by gender. Data were collected from forty-six elementary school principals across multiple districts using a structured survey instrument adapted from the Culturally Responsive Principals Rating Scale (CRPRS). The instrument assessed five domains of culturally responsive leadership: school morale and pulse, ethics of caring, ethics of bonding, relationship building, and teacher effectiveness. Participants responded using a four-point Likert-type scale ranging from “Never” (1) to “Always” (4). For analysis, culturally responsive leadership responses were examined across three reported practice levels: “Sometimes,” “Fairly Often,” and “Always.” Descriptive statistics and cross-tabulation analyses were conducted, followed by a Pearson chi-square test of independence to examine the relationship between principals’ gender and culturally responsive leadership practice levels. Results indicated that most principals reported engaging in culturally responsive leadership practices at the “Fairly Often” level (78.3%, n = 36), followed by “Always” (17.4%, n = 8), with a small percentage reporting “Sometimes” (4.3%, n = 2). No participants reported responses categorized as “Never.” Although female principals reported slightly higher percentages of “Always” responses (23.8%) compared with male principals (12.0%), the association between gender and culturally responsive leadership practice levels was not statistically significant, χ²(2, N = 46) = 2.616, p = .270. The likelihood ratio test yielded a similar nonsignificant result, LR χ²(2, N = 46) = 3.375, p = .185, with a small effect size (Cramér’s V = .24). Findings suggest that principals across gender groups reported consistent engagement in culturally responsive leadership practices. However, interpretations should be considered within the context of the study’s limitations, including the reliance on self-reported data and the relatively small sample size of forty-six elementary principals, which may limit generalizability. The findings reinforce the importance of leadership preparation, ongoing professional learning, and organizational support systems that cultivate culturally responsive leadership capacities. Continued research using larger samples, multiple perspectives, and longitudinal approaches is needed to further examine how principals’ identities, professional experiences, and school contexts influence the enactment of culturally responsive leadership.